From structure topology to chemical composition. IX. Titanium silicates: revision of the crystal chemistry of lomonosovite and murmanite, Group-IV minerals - CAMARA ARTIGAS, Fernando; Sokolova E; Hawthorne FC; Abdu Y. (Mineralogical Magazine, 2008)
The crystal structures of lomonosovite, ideally Na(10)Ti(4)(Si(2)O(7))(2)(PO(4))(2) O(4) a = 5.4170(7) angstrom, b = 7.1190(9) angstrom, c = 14.487(2) angstrom, alpha = 99.957(3)degrees, beta = 96.711(3)degrees, gamma = 90.360(3)degrees, V = 546.28(4) angstrom(3), D(calc). = 3.175 g cm(-3), and murmanite, ideally Na(4)Ti(4)(Si(2)O(7))(2)O(4)(H(2)O)(4), a = 5.3875(6) angstrom, b = 7.0579(7) angstrom, c = 12.176(1) angstrom, alpha = 93.511(2)degrees, beta = 107.943(4)degrees, gamma = 90.093(2)degrees, V = 439.55(2) angstrom(3), D(calc). = 2.956 g.cm(-3), from the Lovozero alkaline massif, Kola Peninsula, Russia, have been refined in the space group P (1) over bar (Z = 1) to R values of 2.64 and 4.47%, respectively, using 4572 and 2222 observed vertical bar F(o) >= 4 sigma F vertical bar reflections collected with a single-crystal Bruker AXS SMART APEX diffractometer with a CCD detector and Mo-K alpha radiation. Electron microprobe analysis gave empirical formulae for lomonosovite (Na(9.50)Mn(0.16)Ca(0.11))(Sigma 9.77)(Ti(2.83)(4+)Nb(0.51)Mn(0.27)(2+)Zr(0.11)Mg(0.11)Fe(0.10)(2+)Fe(0.06)(3+)Ta(0.01))(Sigma 4.00)(Si(2.02)O(7))(2) (P(0.98)O(4))(2)(O(3.50)F(0.50))(Sigma 4), Z = 1, calculated on the basis of 26(O+F) a.p.f.u., and murmanite (Na(3.32)Mn(0.15)Ca(0.21)K(0.05))(Sigma 3.73)(Ti(3.08)(4+)Nb(0.51)Mn(0.18)(2+)Fe(0.15)(3+)Mg(0.07)Zr(0.01))(Sigma 4.00)(Si(1.98)O(7))(2)(O(3.76)F(0.24))(Sigma 4) (H(2)O)(4), Z = 1, calculated on the basis of 22 (O+F) a.p.f.u., with H(2)O determined from structure refinement and Fe(3+)/(Fe(2+)+Fe(3+)) ratios obtained by Mossbauer spectroscopy. The crystal structures of lomonosovite and murmanite are a combination of a titanium silicate (TS) block and an intermediate (I) block. The TS block consists of HOH sheets (H-heteropolyhedral, O-octahedral), and is characterized by a planar cell based on translation vectors, t(1) and t(2), t(1) similar to 5.5 and t(2) similar to 7 angstrom and t(1) boolean AND t(2) close to 90 degrees. The TS block exhibits linkage and stereochemistry typical ...